IMPLEMENTASI MEDIA PEMBELAJARAN KOPUNKA (KOTAK PINTAR MENYUSUN KALIMAT) MENGATASI PERMASALAHAN MENYUSUN KALIMAT SISWA KELAS II DI SD MUHAMMADIYAH 05 BATU - Rizka Hanafiah Putri; Maharani Putri Kumalasani; Arina Restian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In the learning process taking place on the material on the ability to compose sentences in class II of SD Muhammadiyah 05 Batu, there is a problem where students do not understand how to compose sentences correctly according to the elements of SPOK. By using learning media, it is hoped that it can help teachers in providing learning information to students, by building students' learning motivation by learning while playing. Therefore, this research was carried out with the aim of producing kopunka learning media (smart boxes for composing sentences in Indonesian language learning. This research method is a Research and Development (RnD) type of research using the ADDIE model. The data analysis techniques used are qualitative data analysis and data analysis Quantitative There are also research findings in the use of kopunka, it can be concluded that the kopunka learning media (smart box for composing sentences) has an effect on improving the learning process, helping teachers provide students with an understanding of the material, the ability to compose sentences, and increasing students' learning motivation.